Changes in leptin and testosterone hormones associated with Eurycoma Longifolia jack (Tongkat ali) root extract consumption in male rats - Faisal, Ghasak Ghazi; Mustafa Al-Ahmad, Basma Ezzat; Najmuldeen, Ghazi Faisal; Mustafa, Nazih Shaban; Al-Ani, Ali Sabri Radeef; Althunibat, Osama Yousef (2015)
Objectives: To study the effects of Eurycoma Longifolia jack (E.L.) root extract on the serum leptin and testosterone levels of male rats. Methodology: Mature male Albino Wistar rats were used in this study. Serum leptin and testosterone ;levels were analyzed before receiving treatment (control group), then the rats were divided into two groups. Group A received 5mg/kg twice daily of pure E.L. root extract. Group B received 10mg/kg twice daily of the same extract. The duration of treatment was 6 weeks for both groups at the end of which, serum leptin and testosterone levels of both groups were analyzed again. Results: The mean serum leptin and testosterone levels for the control group were 1.13ng/ml, 0.79ng/ml. While for group A were1.08ng/ml, 0.98ng/ml and for Group B were 0.89ng/ml,1.75ng/ml respectively. Statistical analysis showed that the serum leptin level of group B was significantly lower than that of control group (p<0.001) and group A(p<0.05). On the other hand, no significant difference in serum leptin levels was observed between the control group and group A. The serum testosterone level was significantly higher in group B than control and group A while group A did not show a statistically significant difference than control. Conclusion: E.L. root extract can significantly decrease serum leptin and increase serum testosterone levels and these effects are dose dependant.